Repeated-sprint ability and its correlates among handball players in Porto-Novo, Republic of Benin. - GOUTHON, P.; NOUATIN, BK; Messan, F.; ADIDO, C.; TONON, Brigitte Affidéhomé; FALOLA, J-M.; BIO NIGAN, I. (My University, 2015)
Aim. This cross-sectional study aims at iden- tifying, by age groups, the factors which con- tribute most to the prediction of repeated sprint ability (RSA) among handball players in Porto-Novo, Benin. Methods. The study was carried out with 208 players aged 10 to 25, who practise handball at school and/or in civil clubs. Total running time (Tt) and fatigue index (FI) at the RSA test were the dependent variables. Gender, seniority in handball practice, performance at the squat jump, 30-15 IFT, motor coordina- tion test of Illinois, sprint on 30 m tests were the independent or predictive variables. Results. In minim players, the performance at the Illinois test was the ftrst predictive var- iable of Tt (r2=0.42; P=0.002). In the cadet, junior and senior categories, the perform- ance at sprint on 30 m presented the highest r2 of 0.60, 0.45 and 0.40 (P<0.0001). Conclusion. From the two performance cri- teria of the used RSA test, Tt varied most ac- cording to age group and was more associ- ated with other studied variables. Moreover, the factors which contributed more to the prediction of RSA in the Porto-Novo minim handball players (10-12 years) differed from those identifted for older groups.
Keywords: Oxygen consumption - Athletic per- formance - Exercise test.